Migration to the EU: Social and macroeconomic effects on sending countries - D'Artis Kancs; Pavel Ciaian; Julda Kielyte (Economics and Econometrics Research Institute (EERI), 2016)
In June 2016, the European Commission issued a new EU Blue Card proposal. This proposal is meant to make the EU more attractive for highly qualified workers from third countries. While strengthening the knowledge economy of the EU, the potential impacts of the new Blue Card proposal on developing countries are less known. The present study attempts to shed light on potential challenges and opportunities for developing countries by analysing conceptually the potential socio-economic impacts of the new EU Blue Card proposal. Our results suggest that the EU Blue Card may reduce the human capital, the knowledge capital, and hence growth and development prospects in developing countries, if not accompanied by appropriate policy measures. We identify and examine a number of policy measures, which could help turning the sending country challenges into opportunities. Our results suggest that policies implemented on the demand side of the labour market are more efficient than policies that address the supply side of the labour market, though they are less costly to implement. Developing countries can also benefit from the knowledge diffusion from the EU, if sufficient human resources are available to use this knowledge.
Keywords: C68; D58; F22; J20; J61; J64; O15; 330; High-skill migration; EU Blue Card; knowledge-based capital; endogenous growth; developing countries.